A New ARMA G (p, q) Model for largest Viral Replication and its Posterior Distribution - G. Meenakshi , S. Saranya (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A Statistical Models used for quantifying the viral load in the blood plasma of HIV Patients. These Models are mostly non-linear differential equations. Determination of solution of variable in the Differential equation is very complicated. The quantification of viral load by using differential equation is not as easy approach. The hierarchical Bayesian approach is used to find the predictive distribution of viral load, which is other way of finding the solution. If the prior distribution is only conjugate the expression Predictive Distribution is simple. The study of viral replication not at all considering as a single period, it is based on the number of succeeding periods. So, the researcher developed a New Auto Regressive moving average Growth process with (p, q) order for the viral replication and finds its predictive distribution.